Enhancing Quantum Information Processing – SU(2) Operator Model Development for Three-Qubit Quantum Systems Entanglement Classification - Amirul Asyraf Zhahir; Siti Munirah Mohd; Mohd Ilias M Shuhud; Bahari Idrus; Hishamuddin Zainuddin; Nurhidaya Mohd Jan; Mohamed Ridza Wahiddin (Semarak Ilmu Publishing, 2024)
Non-Indexed Publication